Heat Radiation Emanating from Hydrogen and Methane Jet Fires - Christopher Bernardy; Abdel Karim Habib; Martin Kluge; Alessandro Orchini (Chemical Engineering Transactions, 2025)
Modelling the heat radiation emanating from jet flames for initial hazard assessment purposes is generally done using simple, steady-state, approaches that give a quick estimation useful for impact analysis. Although nowadays CFD can be used to simulate this phenomenon in detail, it is still very demanding in computational power and time, and generally not all required boundary conditions to achieve a reliable result are known. Therefore, even today simpler empirical approaches are still widely used for consequence analysis. Hydrogen is becoming increasingly important as renewable energy carrier resulting in an increasing demand of “hydrogen-approved” models. Since the aforenamed models were mainly developed based on data from hydrocarbon jet flame experiments, it has to be verified if they also apply to hydrogen jet flames. To this purpose, real-scale tests are carried out at the BAM Test Site Technical Safety (BAM-TTS) with the aim to assess the flame geometry and the emitted thermal radiation of hydrogen and methane jet flames. In particular, the focus is laid on the measurement and modelling of the thermal radiation. Existing heat radiation data from the literature are mostly based on unsteady outflow conditions. The experimental setup used here allows for the generation of a steady-state outflow and thus a direct comparability with existing (steady-state) models. From these data, an assessment of the applicability of jet flame models to hydrogen jet flames is carried out accounting for their accuracy in predicting heat radiation and possible needs of further development.